Efficient Bidirectional DFE for Doubly Selective Wireless Channels - Tomasin Stefano (EURASIP Journal on Advances in Signal Processing, 2006)
The bidirectional decision feedback equalizer (DFE) performs two equalizations, one on the received signal and one on its time-reversed version. In this paper, we apply the bidirectional DFE to wireless transmissions on rapidly time-varying dispersive channels and we propose an efficient implementation obtained by implementing the feedforward filter in the frequency domain. The feedback filter is adapted to the channel variations within one block and we propose a simplified design of the feedback filter coefficients based on a polynomial model of channel variations. Simulations performed on time-varying channels show that the proposed structure significantly outperforms existing architectures.